Affect and the performative dimension of fear in the Indian English novel : tumults of the imagination - De Riso, Giuseppe (Cambridge Scholars Publishing, 2018)
This volume provides a critical reading of Khushwant Singh's Train to Pakistan (1956), Neel Mukherjee's The Lives of Others (2014) and Rohinton Mistry's A Fine Balance (1995) to provide a literary account of three fundamental moments in India's history: the Partition of 1947, the Naxalbari movement, and Indira Gandhi's Emergency. These novels provide literary interpretations of the ways in which feelings of fear and insecurity connected with ethno-religious rivalries, as well as with new power shifts in Indian socio-economic structure, gave a significant contribution to the formation of the pol.